INTEGRATING SMARTPHONES IN ENGLISH CLASS AT ELEMENTARY SCHOOL LEVEL: A STUDY ON INDONESIAN ELEMENTARY SCHOOL TEACHER’S PERCEPTION - Resti Purnamasari; Metty Agustine Primary; Yuyus Saputra; Rahmat (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Due to the COVID-19 outbreak, it requires that the learning process, including teaching English at the elementary school level, is carried out with an online learning system. Implementing an online learning system is closely related to the use of technology. Smartphones are one of the technological tools that are widely used in facilitating the online learning process. Hence, the study in this article aimed to examine the perception of an elementary school teacher in integrating smartphones during the English teaching process. Based on the research, the researchers used a case study as the research design, along with semi-structured interviews and online observations for data collection. The data were then analyzed using thematic analysis, which was further elaborated with the TPACK framework from Mishra and Koehler (2006). The study reveals two responses related to the teacher’s perception of using smartphones, namely negative and positive responses. The negative responses consist of three perceptions: (1) ineffective delivery of subject materials, (2) difficulties in managing students, and (3) internet access problems. Meanwhile, the positive responses include (1) smartphones as an adequate teaching medium, (2) an affordable platform for teaching, and (3) YouTube channels as an engaging learning resource for young learners. In conclusion, the use of smartphones in teaching English at the elementary school level raised both negative and positive reactions from the teacher during the teaching process. Therefore, teaching English to young learners requires the teacher to adequately integrate technological, pedagogical, and content knowledge.